The Remediation of Congo Red-Contaminated Groundwater by using a Permeable Reactive Barrier Through Modified Waterworks Sludge MgAl-LDH - Salih, Sudad Adil; Naife, Tariq M. (Al-Khwarizmi Engineering Journal, 2023)
This investigation aims to explore the potential of waterworks sludge (WS), low-cost byproduct of water treatment processes, as a sorbent for removing Congo Red (CR) dyes. This will be achieved by precipitating nano-sized (MgAl-LDH)-layered double hydroxide onto the surface of the sludge. The efficiency of utilizing MgAl-LDH to modify waterworks sludge (MWS) for use in permeable reactive barrier technology was confirmed through analysis with Fourier transform infrared and X-ray diffraction. The isotherm model was employed to elucidate the adsorption mechanisms involved in the process. Furthermore, the COMSOL model was utilized to establish a continuous testing model for the analysis of contaminant transport under diverse conditions. A strong correlation was indicated, with a coefficient of determination (R2) ≥ 0.97, when the model’s predictions were compared to experimental values, indicating the accuracy of the model. Continuous transport exhibited earlier breakthrough points when the bed depth decreased and the initial concentration and flow rate increased.